First record of Myxobolus problematicus from gills of Carasobarbus luteus fish from Tigris river, Al-Shawwaka region in Baghdad city, Iraq - Al-Saadi, Abid Ali Jenzeel Jbara; Rasheed, Rabab A. (Journal of Kerbala for Agricultural Sciences, 2018)
A total of 35 specimens of the fish Carasobarbus luteus (Heckel, 1843) were collected from Tigris River in Al-Shawwaka region in Baghdad city. The results showed that fish were found to be infected with five species of parasites, these parasites were Myxobolus chondrostomi, M. problematicus, Dactylogyrus bocageii, D. lenkorani and Procamallanus viviparous. In addition which were M. problematicus considered as a first record in Iraq, as well as C. luteus as a new host in Iraq for these five species of parasites.